Analisis Penerimaan Sistem Digitalisasi Museum Bali Berbasis VT360° Menggunakan Metode MDLC & TAM - Arditaloka, I Wayan Angga; Aris Gunadi, I Gede; Indrawan, Gede (LPPM Universitas Dinamika Bangsa, 2025)
Central Statistics Agency (BPS). Museum Bali has also experienced a decline in visits, especially from local tourists, the management has tried to stimulate public interest through making events that are expected to be able to introduce the museum to the public, but these efforts have not resulted in an increase in visits, on the contrary, the number of visits has decreased. The impact of the decline in visits to Museum Bali is very pronounced, it is not uncommon for not even a single domestic tourist to come in a day. The design of this application aims to bring Museum Bali closer to the younger generation through a virtual tour based on interactive multimedia applications. The research method used in the development of the application being built is the Multimedia Development Life Cycle (MDLC) method using the Technology Acceptance Model (TAM) in analysing the acceptance of the application. In developing this 360° virtual tour application. This study uses 80 data samples obtained from calculations using the Solvin formula. The results showed that 80% of respondents were satisfied and accepted the application that had been designed. The results of convergent validity testing have an average value of 0.79, with an AVE value above 0.50. Composite reliability and Cronbach's Alpha were found to be greater than 0.7 so that the TAM testing of this application falls into the strong category. Keywords: MDLC; TAM; Museum; Virtual Tour; Tourism;